Digital Marketing Strategy in Increasing Bus Ticket Sales at PT Rosalia Indah Transport Surakarta – Central Java - Anggara Putra Bimantara; Lia Nirawati (Universitas KH. Abdul Chalim Mojokerto, 2025)
The Service industry sector has a very important role in economic growth and development. The service industry provides convenience in every aspect of life, both economic aspects, social aspects, and political aspects. Transportation, telecommunications, banking, education, health services, construction services, and tourism are some examples of service industries that play an important role in a nation's economic development. Among the many service businesses currently developing, transportation services are a promising business, both land, sea, and air transportation. In this research, quantitative descriptive methods were used. The data collection method in this research was carried out utilizing observation, interviews, questionnaires, and literature study, and data processing was carried out with the help of the SPSS 25 program. So, the results of the t-test that was carried out in this research were obtained, so it can be concluded that there is an influence that digital marketing strategy variables have on bus ticket sales at PT Rosalia Indah Transport Surakarta-Central Java.